Implementation of Fault Tree Analysis for Production Quality Control Evaluation - Zulfahmi Noor; Nurmasitya Kemalaintan; Muhammad Noor Arridho (Asian Journal Science and Engineering, 2025)
This study aims to evaluate the quality control of lightweight brick production at PT XYZ using the Fault Tree Analysis (FTA) method. In the manufacturing industry, product defects are a major challenge that can affect production efficiency, operating costs, and company competitiveness. Based on production data from January to December 2024, the total number of defects identified reached 125,334 units, consisting of three main types, namely cracks (63%), peeling (21%), and imprecision (16%). Through the application of FTA, this study revealed that the two dominant factors that are the root causes of product defects are human error and tools or equipment. Human error is mainly triggered by operator carelessness, overly rapid mold dismantling processes, and errors in installing cutting tools. Meanwhile, machine factors include worn components, excessive vibration, deteriorating cutting wire quality, and lack of regular maintenance. The results of the study emphasize the need for a comprehensive improvement strategy through increasing operator competence, enforcing work discipline, scheduled machine maintenance, and standardizing operational procedures. The implementation of these improvements is expected to reduce the defect rate and improve product quality in a sustainable manner.